Comparison of Two Intravenous Fluid Maintenance Therapy with Different Sodium Concentrations in Hospitalized Children: A Randomized Trial Study - Fahimi, Dariush; Aghajani Delavar, Motahareh; Karahoudi, Maedeh; Honarmand, Malektaj; Eghbalkhah, Asgar (Journal of Pediatric Nephrology, 2014)
Introduction: Hyponatremia refers to the serum sodium levels less than 135 mEq/L, which can even lead to death. Accordingly, the present study compared the effects of intravenous fluid maintenance treatment with different concentration levels of sodium. Materials and Methods: In an investigative study to evaluate children admitted to the Pediatric Intensive Care Unit (PICU) of Bahrami Children’s Hospital (2012-2013) which required intravenous fluid therapy and aged one to 14 years were evaluated. They were randomly divided into two groups: fluid treatment with 50 mEq/L (group I) and 100 mEq/L (group II) sodium concentrations. The fluids were calculated according to Holliday-Segar formula. Sodium of plasma [P (Na)] and Urine specific gravity (USG) were measured at the time of admittance (first P (Na) and USG) and 24 hrs after treatment (second P (Na) and USG). Results: 108 children were admitted into the study. Significant differences were noted in the second P (Na) levels and differing of first and second P (Na) (P<0.008 and P<0.011). In the first group, 14 cases and in second three cases were hyponatremia (P (Na) < 135 mmol/L), but they weren’t symptomatic during the study. The difference between first and second USG was greater in group I (P <0.023). Conclusions: There was relation between the sodium of the IV fluid and decreased P (Na) concentration in the children who were undergoing intravenous (IV) fluid therapy. There were no Symptomatic hyponatremia cases reported, due to the decrease of P (Na), nor in the 24 hours following the IV therapy treatment. Keywords: Fluid Therapy; Specific Gravity; Sodium; Hyponatremia